A study to find the causes of diabetic foot infections in a selected community - Pallela, Someshwara Rao Narayana; Narahari, Padmavathi (International Surgery Journal, 2017)
Background: Ulcerations associated with diabetes are the most common cause of foot infections. Most of these ulcers are a direct result of loss of sensation secondary to peripheral neuropathy. The prevalence of leg ulceration is approximately 1% to 2%, and is slightly higher in the older adult population. Venous ulcers are the most common form of leg ulcers, accounting for almost 80% of all lower extremity ulcerations. Peak prevalence is between 60 and 80 years. Approximately one third of patients with chronic venous insufficiency will develop venous ulceration before the age of 40 years. In addition, venous ulcers may have a prolonged duration and are associated with a high rate of recurrence, which contributes to their prevalence. Approximately 15% of persons with diabetes will develop foot ulceration during their lifetime. Most lower extremity amputations in India are preceded by a foot ulcer. This study is done to find the commonest causes of foot infection in the background of neuropathy among the selected population. Methods: Total of 153 patients were included in this study. Detailed history was taken and all the wounds were classified according to Wagner’s grades. Foot infections in the grade 3,4, 5 (which required debridement/amputations) were included in the study. Foot ulcerations without infections were excluded from the study. Results: 142 (92%) of the patients with infection had diabetic neuropathy. All patients with diabetic neuropathy presented with sensory neuropathy. 33 (21%) patients presented with infection due to previous callus. 52 (33%) patients presented with infection due to previous non-healing ulcer. 20 (13%) patients with deformities developed callus at bony pressure areas due to neuropathy or post-surgery sequel. One patient had hot water burns injury. Five (0.03%) patients had Ingrown nails. 14 (0.09%) patients related to barefoot walking/thorn prick injuries. 6 (0.03%) patients had fungal infection. Two (0.01%) patients had itching and scratching over legs. 15 (0.09%) patients had history of previous amputation. Vigorous massage was the cause in 1 patient (0.006%). Shoe bite injury resulted in foot ulcer in 2 (0.02%) patients. Two (0.02%) patients presented with infection due to deep cracks in heels. Conclusions: Neuropathic changes is the most common cause of diabetic foot infections among which callus, non-healing trophic ulcer and previous amputee are the predominant causes. Patient education has a crucial role in prevention of diabetic foot infections by foot care precautions.